2008
DOI: 10.1111/j.1600-0447.2008.01266.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive lithium treatment in the prevention of suicidal behaviour in depressive disorders: a randomised, placebo‐controlled, 1‐year trial

Abstract: Results indicate that lithium treatment might be effective in reducing the risk of completed suicide in adult patients with affective disorders. Our findings contribute to the growing body of evidence suggesting a specific antisuicidal effect of lithium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(70 citation statements)
references
References 49 publications
2
61
0
7
Order By: Relevance
“…Several meta-analyses (Cipriani et al, 2005;Baldessarini et al, 2006;Cipriani et al, 2013) and randomized trials (Lauterbach et al, 2008;Oquendo et al, 2011) have shown anti-suicidal effects of lithium in people with mood disorders. Despite the fact that lithium levels in tap water are much lower than the so-called therapeutic levels, accumulating epidemiological studies investigate whether lithium may be effective for suicide attempt.…”
Section: Introductionmentioning
confidence: 99%
“…Several meta-analyses (Cipriani et al, 2005;Baldessarini et al, 2006;Cipriani et al, 2013) and randomized trials (Lauterbach et al, 2008;Oquendo et al, 2011) have shown anti-suicidal effects of lithium in people with mood disorders. Despite the fact that lithium levels in tap water are much lower than the so-called therapeutic levels, accumulating epidemiological studies investigate whether lithium may be effective for suicide attempt.…”
Section: Introductionmentioning
confidence: 99%
“…Additional proof comes from the first controlled trial with lithium versus placebo as an adjunctive treatment in a large sample of high-risk patients. Suicidal events were defined as the endpoint [32] . Whereas the number of suicide attempts did not differ between treatment groups, a statistically significant superiority of lithium in terms of completed suicides was observed, whereas in a retrospective chart review of long-term treated bipolar patients from a single private practice nonfatal suicidal behavior was not different in patients on lithium and those on anticonvulsants [33] .…”
Section: Further Studies and Meta-analysesmentioning
confidence: 99%
“…Another slightly larger RCT of lithium versus placebo was conducted by Lauterbach 24 in 2008 in 167 depressed patients. This study included patients at higher risk for suicide, enrolling only those with a recent suicide attempt (<3 months).…”
Section: Lithiummentioning
confidence: 99%
“…22 Other similarly conducted meta-analyses have yielded concordant results. 23,24 The case for lithium as a suicide prevention agent in patients with bipolar disorder who are at risk for suicide is a relatively strong one, based on limited RCTs and cohort studies. However, the magnitude of this protective effect, the generalizability of this effect to other mental disorders, and the risk–benefit profile of its widespread use primarily as a suicide risk–mitigating agent are all topics for further debate and study.…”
Section: Lithiummentioning
confidence: 99%